THE HYBRID PERSEMBAHAN DANCE: CROSS-CULTURAL COLLABORATION AND ART TOURISM IN PASA HARAU ART AND CULTURE FESTIVAL 2018 - Fresti Yuliza; Visaka Saeui; Hasnah Sy; Dede Pramayoza (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
This paper discusses the process of creating a collaborative dance work entitled Cross-Cultural Offering Dance, which was created jointly by three choreographers of different cultural backgrounds in the 2018 Pasa Harau Art and Culture Festival. The three choreographers involved in the collaboration are Siska Aprisia (Minangkabau, Indonesia). ), Kiki Rahmatika Syaher (Lampung, Indonesia), and Visaka Saeui (Thailand). The three of them tried to create a dance offering by offering the idea of a dance with the same theme, namely a dance to welcome guests in their respective cultural backgrounds. Applying a qualitative approach with research methods centered on performance events, this paper is intended to describe the stages of the creation process, and the modes of collaboration agreed upon by the three choreographers. Primary data was collected through involved observation, namely by participating directly as a choreographer, dramaturg, and administrator of the intended collaborative dance performance process. Secondary data were collected from narrative interviews with the three choreographers and by observing the responses and reactions of the audience and dancers. The results showed that the creation of the Performance Dance by the three choreographers was a hybridization process that began with sharing views on the world of traditional dance in order to build a shared spectrum, followed by a process of division of parts in the plot, where the embodiment of the atmosphere from solemn to joyful became the common thread. The result of the collaboration is a dance number entitled Cross-Cultural Offering Dance, which not only meets the criteria as a presentation in a festival, but can also be a tourism art presentation.Keywords: Persembahan Dance; Hybrid; Cross-Cultural Collaboration; Tourism Arts; FestivalTARI PERSEMBAHAN HIBRIDA: KOLABORASI LINTAS-BUDAYA DAN SENI PARIWISATA DALAM PASA HARAU ART AND CULTURE FESTIVAL 2018AbstrakTulisan ini membahas tentang proses penciptaan sebuah karya tari kolaboratif bertajuk Tari Persembahan Lintas Budaya, yang diciptakan bersama oleh tiga koreografer berbeda latar belakang budaya dalam kegiatan Pasa Harau Art and Culture Festival 2018. Ketiga koreografer yang terlibat di dalam kolaborasi adalah Siska Aprisia (Minangkabau, Indonesia), Kiki Rahmatika Syaher (Lampung, Indonesia), dan Visaka Saeui (Thailand). Ketiganya mencoba menciptakan sebuah karya Tari Persembahan dengan menawarkan gagasan dari tari bertema sama, yakni tari penyambutan tamu di masing-masing latar budaya mereka. Menerapkan pendekatan kualitatif dengan metode penelitian yang berpusat pada peristiwa pergelaran, tulisan ini dimaksudkan untuk menguraikan perihal tahapan-tahapan proses penciptaan, dan moda kolaborasi yang disepakati oleh ketiga koreografer. Data primer dikumpulkan melalui pengamatan terlibat, yakni dengan ikut serta secara langsung sebagai koreografer, dramaturg, dan administrator dari proses kolaborasi Tari Persembahan yang dimaksudkan. Data sekunder dikumpulkan dari wawancara naratif dengan ketiga koreografer serta dengan mengamati respons dan reaksi penonton dan penari. Hasil penelitian menunjukkan bahwa penciptaan Tari Persembahan oleh ketiga orang koreograger adalah suatu proses hibridisasi yang dimulai dengan sharing pandangan atas dunia tari tradisional guna membangun spektrum bersama, dilanjutkan dengan proses pembagian bagian dalam plot, di mana perwujudan suasana dari khidmat menuju riang gembira menjadi benang merahnya. Hasil dari kolaborasi adalah sebuah nomor tarian bertajuk Tari Persembahan Lintas Budaya, yang tidak saja memenuhi kriteria sebagai sajian dalam festival, namun juga dapat menjadi sajian seni pariwisata.Kata Kunci: Tari Persembahan; Hibrida; Kolaborasi Lintas-Budaya; Seni Pariwisata; Festival